The Association Between Acylcarnitine Metabolites and Cardiovascular Disease in Chinese Patients With Type 2 Diabetes Mellitus - Zhao, Shuo; Feng, Xiao-Fei; Huang, Ting; Luo, Hui-Huan; Chen, Jian-Xin; Zeng, Jia; Gu, Muyu; Li, Jing; Sun, Xiao-Yu; Sun, Dan; Yang, Xilin; Fang, Zhong-Ze; et al. (Frontiers in Endocrinology, 2020)
Abstract Objective: The association between acylcarnitine metabolites and cardiovascular disease (CVD) in type 2 diabetes mellitus (T2DM) remains uncertain. This study aimed to investigate associations between acylcarnitines and CVD in Chinese patients with T2DM. Methods: A cross-sectional study was conducted from May 2015 to August 2016. Medical records of 741 patients with T2DM were retrieved from the main electronic database of Liaoning Medical University First Affiliated Hospital. CVD was defined as having either coronary artery disease (CAD) or heart failure (HF) or stroke. Mass Spectrometry was utilized to measure levels of 25 acylcarnitine metabolites in fasting plasma. Factor analysis was used to reduce the dimensions and extracted factors of the 25 acylcarnitine metabolites. Multivariable binary logistic regression was used to obtain odds ratios (OR) of the factors extracted from the 25 acylcarnitine metabolites and their 95% confidence intervals (CI) for CVD. Results: Of the 741 patients with T2DM, 288 had CVD. Five factors were extracted from the 25 acylcarnitines and they accounted for 65.9% of the total variance. Factor1 consisted of acetylcarnitine, butyrylcarnitine, hydroxylbutyrylcarnitine, glutarylcarnitine, hexanoylcarnitine, octanoylcarnitine and tetradecanoyldiacylcarnitine. Factor 2 consisted of decanoylcarnitine, lauroylcarnitine, myristoylcarnitine, 3-hydroxyl-tetradecanoylcarnitine, tetradecenoylcarnitine and 3-hydroxypalmitoylcarnitine. After adjusting for potential confounders, increased factor 1 and factor 2 were associated with increased risks of CVD in T2DM (OR of factor 1: 1.45, 95%CI: 1.03-2.03; OR of factor 2: 1.23, 95%CI: 1.02-1.50). Conclusions: Elevated plasma levels of some acylcarnitine metabolites, i.e., those extracted into factor 1 and factor 2, were associated with CVD risk in T2DM.